The Effects of Branding Intangibles on Corporate Reputation. - Orozco -Toro, Jaime Alberto (2019)
This paper focuses on the problem of Corporate Reputation in relation to stakeholders’ perception. More precisely, how the intangible values of branding have a potential influence on the Corporate Reputation of a communication company. As fieldwork, with the aim of having contact with the complete value chain of a corporation, 463 questionnaires conducted with members from all the stakeholder groups (7) of Televisió de Catalunya–TV3 regarding La Marató de TV3 have been analyzed. La Marató action is a Corporate Social Responsibility event organized by the autonomous public television network of Catalonia (Barcelona, Spain). The results allow us to identify how trust, quality, transparency and solidarity are the most important values identified in its corporate reputation. This research is relevant as it studies the role of and relationship between intangible values of branding and the perception of corporate reputation in a complete company value chain (representing all its stakeholders).